`This Thing Called a Bank': Swift's Proposal for the Universal Use of Irish Manufacture and the 1720 national bank proposals - Walsh, Patrick (My University, 2025)
This article revisits Jonathan Swift’s Proposal for the Universal Use of Irish Manufacture (1720) and seeks to place it within the context of the debates surrounding the proposed establishment of an Irish national bank in 1720. It shows how Swift’s discussion of the ills facing the Irish economy might be placed in conversation with the projects for a bank. In doing so it both takes Swift’s commentary on the bank seriously and speculates that it may have been an addendum to the original text of the pamphlet. Engaging with recent Swift scholarship and the literature on the bank it shows how the Dean’s arguments fitted into wider arguments and the economic future of a dependent province and how these debates were fundamentally shaped and reshaped by the wider context of the South Sea Bubble.
PUBLISHED
Keywords: Making Ireland; Manuscript, Book and Print Cultures; 18h century Irish history; Economic History; Irish History; Jonathan Swift; Urban and economic history